Kebijakan Penenggelaman Kapal Pelaku IUU Fishing di Indonesia dalam Pencapaian Target Tujuan Pembangunan Berkelanjutan - Kusuma, Brian Tri; Aryani, Maria Indira (Global and Policy Journal of International Relations, 2023)
The ship sinking policy is one of Indonesia's steps to eradicate Illegal, Unreported, Unregulated Fishing, this policy was intensively carried out during the leadership of Susi Pudjiastuti as Minister of Maritime Affairs and Fisheries in 2014-2019, the first period President Joko Widodo took office. In addition to combating IUU Fishing, this policy is in accordance with the 3 components of Blue Economy activities, which are resource health, trade of resources, and harvesting of living resources. This policy is also a step for Indonesia to implement several targets of Sustainable Development Goals 14 because in addition to stopping and giving a deterrent effect to foreign ships that try to catch fish in Indonesian territory, this policy also has an impact on the preservation of Indonesia's marine nature just like the three targets of Sustainable Development Goals 14. This research uses a qualitative analysis method of secondary data derived from literature studies. The results of this study show the connection between the policy of sinking IUU Fishing vessels and the achievement of Sustainable Development Goals targets in accordance with the Blue Economy Concept. Keywords: Sustainable Development Goals, Ship Sinking Policy, Blue Economy, IUU Fishing Kebijakan penenggelaman kapal merupakan salah satu langkah Indonesia memberantas Illegal, Unreported, Unregulated Fishing, kebijakan ini gencar dilakukan pada masa kepemimpinan Susi Pudjiastuti sebagai Menteri Kelautan dan Perikanan tahun 2014-2019, periode pertama Presiden Joko Widodo menjabat. Selain memerangi pelaku IUU Fishing kebijakan ini sesuai dengan 3 komponen aktivitas Blue Economy yaitu kesehatan sumber daya, perdagangan sumber daya, dan pemanenan sumber daya hayati. Kebijakan ini juga menjadi langkah Indonesia melaksanakan beberapa target capaian Sustainable Development Goals 14 karena selain menghalau dan memberi efek jera pada kapal asing yang mecoba untuk menangkap ikan di wilayah Indonesia, kebijakan ini juga memiliki dampak kepada pelestarian alam laut Indonesia sama seperti tiga target capaian Sustainable Development Goals 14. Penelitian ini menggunakan metode analisis kualitatif data sekunder yang berasal dari studi pustaka. Hasil dari penelitian ini menunjukkan hubungan dan keterkaitan antara kebijakan penenggelaman kapal ikan pelau IUU Fishing terhadap pencapaian target Sustainable Development Goals sesuai dengan konsep Blue Economy. Kata Kunci: Tujuan Pembangunan Berkelanjutan, Kebijakan Penenggelaman Kapal, Ekonomi Biru, IUU FishingDOI: https://doi.org/10.33005/jgp.v11i01.4174